Pembaharuan Hukum Di Dalam Perjanjian Perkawinan - Jamaludin (Al Ashriyyah, 2019)
Marriage Agreement has been regulated in Law Number 1 of 1974 specifically article 29. Marriage Agreement is the right of each party to enter into a marriage agreement. The background of entering into an agreement is their respective rights. With the holding of the Marriage Agreement there is legal certainty about what was promised by them to do a legal action against what was promised. After the decision of the Constitutional Court Number 69 / PUU-XIII / 2015, the Marriage Agreement which can only be made by prospective husbands and future wives before the prenuptal agreement, through legal renewal, can be made by husband and wife after the marriage takes place.